Teoretyczne zasady kategoryzacji skladowych rytmizacji ruchów i ich implikacje dla gier zespolowych oraz innych dyscyplin sportowych - Stronczynski, W.; Starosta, W. (Medycyna sportowa, 2001)
Co-ordination abilities play a leading role in achieving of a high level of technical and tactical proficiency in team games and in other sports. Among the most important ones is the ability of movement rhythmisation. That sport-specific ability is one of the basic determinants of sport technique development. Inasmuch that ability is a key factor in the technical and tactical efficacy of athletes, team game coaches seem not to be aware of it, and rank movement rhythmisation lowest among other co-ordination abilities. Movement rhythmisation was discussed only occasionally, where its appearance was obvious, e.g. in callisthenics. Those features were, so far, not associated with team games or with other sports. The aim of this paper was thus to arrange the components of movement rhythmisation in a logical order, subject to sport specificities. In consequence, sports were classified into groups according to the types of movement rhythm control and for team games and other sports the contributions of modes of movement rhythm control were established.